Anti-Influenza Activity of Marchantins, Macrocyclic Bisbibenzyls Contained in Liverworts - Iwai, Yuma; Murakami, Kouki; Gomi, Yasuyuki; Hashimoto, Toshihiro; Asakawa, Yoshinori; Okuno, Yoshinobu; Ishikawa, Toyokazu; Hatakeyama, Dai; Echigo, Noriko; Kuzuhara, Takashi (PLOS ONE, 2011)
The H1N1 influenza A virus of swine-origin caused pandemics throughout the world in 2009 and the highly pathogenic H5N1 avian influenza virus has also caused epidemics in Southeast Asia in recent years. The threat of influenza A thus remains a serious global health issue and novel drugs that target these viruses are highly desirable. Influenza A possesses an endonuclease within its RNA polymerase which comprises PA, PB1 and PB2 subunits. To identify potential new anti-influenza compounds in our current study, we screened 33 different types of phytochemicals using a PA endonuclease inhibition assay in vitro and an anti-influenza A virus assay. The marchantins are macrocyclic bisbibenzyls found in liverworts, and plagiochin A and perrottetin F are marchantin-related phytochemicals. We found from our screen that marchantin A, B, E, plagiochin A and perrottetin F inhibit influenza PA endonuclease activity in vitro. These compounds have a 3,4-dihydroxyphenethyl group in common, indicating the importance of this moiety for the inhibition of PA endonuclease. Docking simulations of marchantin E with PA endonuclease suggest a putative “fitting and chelating model” as the mechanism underlying PA endonuclease inhibition. The docking amino acids are well conserved between influenza A and B. In a cultured cell system, marchantin E was further found to inhibit the growth of both H3N2 and H1N1 influenza A viruses, and marchantin A, E and perrotein F showed inhibitory properties towards the growth of influenza B. These marchantins also decreased the viral infectivity titer, with marchantin E showing the strongest activity in this assay. We additionally identified a chemical group that is conserved among different anti-influenza chemicals including marchantins, green tea catechins and dihydroxy phenethylphenylphthalimides. Our present results indicate that marchantins are candidate anti-influenza drugs and demonstrate the utility of the PA endonuclease assay in the screening of phytochemicals for anti-influenza characteristics.